Effect of variation in seat tube angle at different seat heights on submaximal cycling performance in man - Price, D.; Donne, B. (Journal of Sports Sciences, 1997)
The effect of seat tube angle at selected seat heights (96, 100 and 104% trochanteric height) on heart rate, VO2 and lower limb kinematics was evaluated in 14 competitive male road racing cyclists during discontinuous submaximal exercise (200 W) on an air-resistance ergometer at seat tube angles of 68, 74 and 80°. The tests were randomized to complete the nine combinations (three seat heights, three tube angles) in opposite directions from a starting tube angle of 74° and 100% trochanteric height to avoid any time or sequence bias. Power efficiency was calculated for each combination from work done and VO2. All results were analysed using ANOVA for repeated measures. At a seat tube angle of 80°, mean VO2 was significantly lower and power efficiency significantly higher compared with an angle of 74° at all three seat heights, while heart rate was significantly lower only at a seat height equal to trochanteric height. At a seat tube angle of 74°, mean VO2 and heart rate were significantly lower and power efficiency significantly higher compared with an angle of 68° at all three seat heights. Hip range of movement and maximum and minimum hip angle were significantly less at an angle of 80° compared with 68°. Further biomechanical analysis suggested that the improvement in cycling efficiency observed at steeper seat tube angles was produced in part by the resultant altered ankling pattern of the cyclist.